An Analysis of Fiscal Policy and Wagner's Law in the Context of Nepal - Acharya, Sabitri Devi (Journal of Development and Administrative Studies, 2021)
There is a lot of discussion among economists about the relationship between expenditure of the government and gross domestic product (GDP). The paper seeks to examine the association between GDP and government expenditure by utilizing the concept of Wagner’s Law. Both long run and short run relationships are examined by use of popular econometric techniques. From the result of Engle-Granger test the significance of Wagner's law is found in the context of Nepal when taking governance and government capital expenditure as the independent variables of economic growth. It has been found that when GDP increases by one percent, capital spending rises by 0.4 percent in the long run. However, the Granger causality test does not reveal any causal relationship between the variables of interest.